Inflammation markers as risk factors of edematous pancreatitis development providing of genetic determination of IL-4 production - Ivashchuk, S. I.; Sydorchuk, L. P. (Journal of Education, Health and Sport, 2017)
Introduction. The powerful mechanism of the immune system involvement in the pathogenesis of acute pancreatitis (AP) and exacerbation of chronic pancreatitis (ECP), especially from the positions of influence of polymorphism of genes which regulate the inflammatory response (interleukin -1β (IL-1β), -4 (IL-4), -6 (IL -6) and tumor necrosis factor-alpha (TNF-α), and others.) on the clinical course of pancreatitis still stays outside the attention of researchers. Objective. The objective of our investigation was to study some indicators of systemic inflammatory response (TNF-α, IL-1β, CRP and a1-AT) in patients with AP and ECP depending on the gene interleukin 4 (IL-4, (C-590T). Materials and methods. The study involved 101 patients with AP and ECP. Molecular genetic studies included the determining of polymorphic variants of gene IL-4 (C-590T). The levels of interleukins IL-4, IL-1β and the tumor necrosis factor - alpha (TNF-α), CRP and a1-AT were determined. Results. Past studies concerning the levels of IL-4 production caused by gene IL-4 polymorphism, established the lower production of IL-4 in the TT-genotype owners of the gene IL-4 (3.78 pg/ml vs. 31.91 and 19.31 pg/ml of CC- and CT-genotypes owners, respectively; pСС<0.001, pСТ<0.01). TNF-α concentration was higher in the carriers of the wild allele C-590T of gene IL-4 polymorphism (11.25 and 10.54 pg/ml vs. 4.80 pg/ml of TT-genotype owners, respectively, Mann-Whitney criterion - 4.87, рСС<0.001, рСТ=0.002). The high concentration of IL-1β in peripheral blood serum was found in 7.69% of T-allele carriers and 34.67% of the owners of C-allele of C-590T polymorphism of gene IL-4 among AP patients (p=0.008). The frequency of patients with a higher concentration of CRP (>10 mg/ml) and a1-AT between allele carriers of gene IL-4 (T- vs. C-allele) did not differ significantly: 61.54% vs. 70.67% (p>0.05) and 34.61% vs. 28.0% (p>0.05), respectively. Conclusions. The increased production of IL-1β is a risk factor for AP in the C-allele carriers of IL-4 gene and protective factor of AP development in T-allele carriers of IL-4 gene (rs2243250) selected polymorphism.